FINANCIAL PERFORMANCE BEFORE AND AFTER THE IMPLEMENTATION OF GOVERNMENT REGULATION NUMBER 109 OF 2012 AT PT. GUDANG GARAM Tbk. DANPT. HM SAMPOERNA Tbk. - Karmila, Karmila (Jurnal Manajemen Dan Bisnis, 2024)
The purpose of this research is to find out whether the Financial Performance of PT. Gudang Garam Tbk. and PT. HM Sampoerna Tbk. experienced a decline after the implementation of Government Regulation Number 109 of 2012. Data analysis used in this research used quantitative descriptive methods by comparing financial ratios consisting of liquidity, solvency, activity and profitability ratios. The research results show that the financial performance of PT. Gudang Garam Tbk. and PT. HM Sampoerna Tbk. tended to decline after the implementation of Government Regulation Number 109 of 2012.